UK Borderscapes (Routledge, 2023)
This book analyses bordering practices and their negative effects as well as the many creative and often grassroots ways in which borders are resisted and reinvented. From the hostile environment to Brexit and the Nationality and Borders Bill, the UK border regime has become increasingly strict and complex, operating both at the edge of the state and within everyday life in unprecedented ways. At the same time, this securitisation approach is often contested, and its effects are fought daily by many groups and individuals. This book explores this tension, documenting and analysing how the contemporary UK border is imagined, constructed, deconstructed, and reconstructed in multiple ways. To draw together the different pieces that compose this evolving and conflicting landscape, this book uses the concept of "borderscapes", which views borders as sites of multiple tensions between hegemonic, non-hegemonic, and counter-hegemonic imaginaries and practices. This lens enables contributors to draw a multifocal overview of the UK border that includes the different human and material actors that form it, the spaces and practices they shape, and the imaginaries and counter-imaginaries that emerge from their conflictual encounters. Bringing together contributions by researchers from a variety of disciplines, this book will be of interest to scholars and students in the fields of migration and border studies, refugee studies, human geography, criminology, sociology, and anthropology.